OsNAC2 positively affects salt‐induced cell death and binds to the OsAP37 and OsCOX11 promoters. (23rd March 2018) - Mao, Chanjuan; Ding, Jialin; Zhang, Bin; Xi, Dandan; Ming, Feng
Summary: Plant development and adaptation to environmental stresses are intimately associated with programmed cell death (PCD). Although some of the mechanisms regulating PCD [e.g., accumulation of reactive oxygen species (ROS)] are common among responses to different abiotic stresses, the pathways mediating salt‐induced PCD remain largely uncharacterized. Here we report that overexpression of OsNAC2, which encodes a plant‐specific transcription factor, promotes salt‐induced cell death accompanied by the loss of plasma membrane integrity, nuclear DNA fragmentation, and changes to caspase‐like activity. In OsNAC2 ‐knockdown lines, cell death was markedly decreased in response to severe salt stress. Additionally, OsNAC2 expression was enhanced in rice seedlings exposed to a high NaCl concentration. Moreover, the results of quantitative real‐time PCR, chromatin immunoprecipitation, dual‐luciferase, and yeast one‐hybrid assays indicated that OsNAC2 targeted genes that encoded an ROS scavenger ( OsCOX11 ) and a caspase‐like protease ( OsAP37 ). Furthermore, K + ‐efflux channels ( OsGORK and OsSKOR ) were clearly activated by OsNAC2. Overall, our results suggested that OsNAC2 accelerates NaCl‐induced PCD and provide new insights into the mechanisms that affect ROS accumulation, plant caspase‐like activity, and K + efflux. Significance Statement: We have uncovered a previously unknown molecular pathway regulating salt‐induced PCD in plants. Our findings also provide clues regarding the possible roles of NAC TFs during stress‐induced PCD across diverse plant species.